Platelet adhesion on endothelium early after vein grafting mediates leukocyte recruitment and intimal hyperplasia in a murine model - Tseng, Chi-Nan; Chang, Ya-Ting; Lengquist, Mariette; Kronqvist, Malin; Hedin, Ulf; Eriksson, Einar E. (Thrombosis and Haemostasis, 2015)
Intimal hyperplasia (IH) is the substrate for accelerated atherosclerosis and limited patency of vein grafts. However, there is still no specific treatment targeting IH following graft surgery. In this study, we used a mouse model of vein grafting to investigate the potential for early intervention with platelet function for later development of graft IH. We transferred the inferior vena cava (IVC) from donor C57BL/6 mice to the carotid artery in recipients using a cuff technique. We found extensive endothelial injury and platelet adhesion one hour following grafting. Adhesion of leukocytes was distinct in areas of platelet adhesion. Platelet and leukocyte adhesion was strongly reduced in mice receiving a function-blocking antibody against the integrin αIIbβ3. This was followed by a reduction of IH one month following grafting. Depletion of platelets using antiserum also reduced IH at later time points. These findings indicate platelets as pivotal to leukocyte recruitment to the wall of vein grafts. In conclusion, the data also highlight early intervention of platelets and inflammation as potential treatment for later formation of IH and accelerated atherosclerosis following bypass surgery.
Keywords: Endothelium; integrin αIIbβ3; leukocyte recruitment; platelet adhesion; leukocyte-platelet interaction